Project Based Learning Arabic Semantic Learning Based on Open Journal Systems at University - Busro, Muh (Study Program of Arabic Language Teaching, 2024)
This study aims to identify the steps of Project Based Learning Arabic Semantic Learning Based on the Open Journal Systems for PBA INSURI Ponorogo students. The research method used is qualitative with a case study model. The research data is from student Arabic Semantic lecture activities using the Project Based Learning method. Data collection techniques using observation and documentation. The data analysis is presented with data reduction, data presentation, conclusion drawing, and verification. The results showed; The stages of Semantic Learning with the Project-Based Learning model using the Open Journal System Platform are Introduction to Topics and Objectives, Explanation and Orientation, Project Planning, Project Implementation, Presentation of Results, Reflection and Evaluation, Integration with the Curriculum, and Awards and Rewards. In the context of the Arabic Language Education Study Program at INSURI Ponorogo, applying PjBL in semantic learning can provide a deep and applicable learning experience. By utilizing the Open Journal System (OJS), students can contribute to peer reviews of journal articles while understanding semantic concepts in Arabic.